2010
DOI: 10.1111/j.1749-4486.2010.02176.x
|View full text |Cite
|
Sign up to set email alerts
|

ORIGINAL ARTICLE: The relationship between patients’ perception of the effects of neurofibromatosis type 2 and the domains of the Short Form‐36

Abstract: The Short Form-36 questionnaire has allowed us to relate patients' perceptions of their difficulties, as identified by the closed set NF2 questionnaire, to the physical and mental domains measured by this validated and widely used scale, and has provided further insight into areas of functioning affected by NF2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 7 publications
1
18
0
Order By: Relevance
“…Few studies have examined the significance of hearing loss on quality of life in the NF2 population. Recently, Neary et al (18) noted that patients with NF2 perceive that hearing loss has a significant ef-fect on the quality of their lives. Specifically, significant effects with respect to hearing difficulties were noted in the physical functioning, bodily pain, general perception of health, social functioning, and role limitations due to emotional problems domains of the SF-36 questionnaire.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have examined the significance of hearing loss on quality of life in the NF2 population. Recently, Neary et al (18) noted that patients with NF2 perceive that hearing loss has a significant ef-fect on the quality of their lives. Specifically, significant effects with respect to hearing difficulties were noted in the physical functioning, bodily pain, general perception of health, social functioning, and role limitations due to emotional problems domains of the SF-36 questionnaire.…”
Section: Discussionmentioning
confidence: 99%
“…Previous investigations of patients with NF1 and NF2 have used both generic and disease‐specific measures to demonstrate that neurofibromatosis patients have a reduced quality of life (QOL) [Wolkenstein et al, ; Page et al, ; Kodra et al, ; Neary et al, ]. Studies using the Short Form‐36 (SF‐36) have correlated lower QOL with increased disease severity in patients with NF1, and with communication, balance, and hearing difficulties in patients with NF2 [Wolkenstein et al, ; Neary et al, ]. However, no studies to date have investigated the possible relationship between internal nerve sheath tumors and QOL in NF patients.…”
Section: Introductionmentioning
confidence: 99%
“…Research with non-NF patient populations also highlights the emotional distress that may accompany chronic medical conditions. 5 To date, however, research regarding the potential psychological impact of NF in adulthood has been generally restricted to a few studies that have examined quality of life among patients with NF1 68 or NF2 9 and to a few that have assessed psychiatric morbidity among patients with NF1 only. 10–12 For example, 12-year follow-up of 48 Swedish patients with NF1 (37 were evaluated for psychiatric disorders at follow-up) found that one-third of the patients met criteria for at least one psychiatric disorder.…”
Section: Introductionmentioning
confidence: 99%